(untitled) (El-Wahat Journal for Research and Studies, 2025)
Talking about the marginalized class is the primary concern of all types of media, and politicians are the main subject of their campaigns and speeches and a tough challenge for their programs. The phenomenon is often treated politically as if it concerns only the state and the political group in society, while the role of individuals and civil society is neglected. In this article, although we recognize the importance of the political and economic dimension, we want to highlight other dimensions in the formation of this phenomenon, because we want to know what are the dimensions of social exclusion in society Algerian and what are its manifestations? This knowledge is necessary to recreate a collective awareness of the effectiveness of individuals and civil society in the reformulation of the system of values and norms regulating life and social relations at the individual and institutional levels in the direction of maximizing the respect, mutual appreciation and cooperation. Key words: Social exclusion, Acknowledgement, Algerian society, Marginalized class, Dangerous neighborhoods